DEVELOPMENT OF THE SYSTEM OF SOCIAL PROTECTION IN UKRAINE IN THE CONTEXT OF EUROPEAN CHOICE - PASICHNYK, Yurii; SUKACH, Olena (Journal of European Economy, 2023)
The article studies basic principles in the functioning of national social protection systems, including the problems and their causes, offers an analysis of their pragmatic applications over the period from 2015 to 2020 and performs a comparison of the calculated euro-denominated social expenditure per person and total social expenditure indicators for Ukraine and several European countries selected to represent the four regions of the EU. Based on the results of performed analysis, it was found that the level of social protection development in Ukraine is lagging far behind all the EU countries, including the least performing ones. Taking into consideration the European experience and Ukraine’s countryspecific features, the authors provide substantiation for the main components of the national social protection model. The developed model includes the current and strategic directions of its development, the interactions between its elements, and the financial resources. The model also takes into account the impact of the factors of external environment, as well as Ukraine’s orientation towards proEuropean development objectives. JEL: H41, H53, H75, I31.